Relative wealth, subjective social status, and their associations with depression: Cross-sectional, population-based study in rural Uganda - Smith, Meghan L.; Kakuhikire, Bernard; Baguma, Charles; Rasmussen, Justin D.; Perkins, Jessica M.; Cooper-Vince, Christine; Venkataramanif, Atheendar S.; Ashaba, Scholastic; Bangsberg, David R.; Tsai, Alexander C. (SSM-population health, 2019)
Depression is a leading cause of disability worldwide, and has been found to be a consistent correlate of socioeconomic status (SES). The relative deprivation hypothesis proposes that one mechanism linking SES to health involves social comparisons, suggesting that relative SES rather than absolute SES is of primary importance in determining health status. Using data from a whole-population sample of 1,620 participants residing in rural southwestern Uganda, we estimated the independent associations between objective and subjective relative wealth and probable depression, as measured by the depression subscale of the Hopkins Symptom Checklist (HSCLD). Objective relative wealth was measured by an asset index based on information about housing characteristics and household possessions, which was used to rank study participants into quintiles (within each village) of relative household asset wealth. Subjective relative wealth was measured by a single question asking participants to rate their wealth, on a 5-point Likert scale, relative to others in their village. Within the population, 460 study participants (28.4%) screened positive for probable depression. Using Poisson regression with cluster-robust error variance, we found that subjective relative wealth was associated with probable depression, adjusting for objective relative wealth and other covariates (adjusted relative risk [aRR] comparing lowest vs. highest level of subjective relative wealth = 1.90, 95% confidence interval [CI]: 1.18, 3.06). Objective relative wealth was not associated with probable depression (aRR comparing lowest vs. highest quintile of objective relative wealth = 1.09, 95% CI: 0.77, 1.55). These results suggest that, in this context, subjective relative wealth is a stronger correlate of mental health status compared with objective relative wealth. Our findings are potentially consistent with the relative deprivation hypothesis, but more research is needed to explain how relative differences in wealth are (accurately or inaccurately) perceived and to elucidate the implications of these perceptions for health outcomes.
Keywords: Depression;Health inequality;Income inequality;Relative deprivation; hypothesis;Social determinants of healt; Subjective wealth;Wealth